AKTIVITAS ANTINEFROLITIASIS EKSTRAK ETANOL DAUN SAMBUNG NYAWA [Gynura procumbens (LOUR.) MERR.] PADA TIKUS PUTIH JANTAN (Rattus norvegicus) - Evalina Tarigan, Rida; Mayanti, Tri; Andry, Muhammad; Surbakti, Chemayanti (Media Penelitian dan Pengembangan Kesehatan, 2023)
Gynura procumbens is a diuretic plant that has been used traditionally to cure kidney stones. In order to determine the calcium levels in the rats' kidneys, the anti-nephrolithiasis activity of male white rats was tested in this study.This research method was carried out experimentally in a laboratory which included sampling, plant identification, making simplicia, making ethanol extract of sambung nyawa leaves, characteristics of simplicia, phytochemical screening, administering animal test preparations, then the data was analyzed using the Anova test. Oral administration of succulent leaf extract is done at three different doses: 50, 100, and 200 mg/kg bw. A positive control is provided with Batugin elixir, which is 0.54 mL/125 g BW and induced at a volume of 7.5 mL/125 g BW/day using ethylene glycol 0.75% and ammonium chloride 2%. The study's findings demonstrated that, with a kidney stone inhibitor percentage of 31.71%, the ethanol extract of Sambung Nyawa leaves at a dose of 200 mg/kg BW was more successful in preventing the formation of kidney stones than doses of 50 mg/kg BW and 100 mg/kg BW. This proves that the ethanol extract from Sambung Nyawa leaves can be an alternative way to prevent kidney stones. The conclusion is that the ethanol extract of Gynura procumbens L. leaves has antinephrolithiasis activity in male white rats, especially at a dose of 200 mg/kg BW. It also reduced calcium oxalate levels in mice induced by ethylene glycol and ammonium chloride.